(untitled) (Journal of Information Technologies in Education (ITE), 2013)
The paper considers some problems and technologies of teaching geometry using dynamic geometry environments to students of advanced classes and specialized study of mathematics. The author emphasizes the urgency of creating computer-oriented technologies and related training programs and system research of the effectiveness of their application considering educational risks.